Sex Education for Individuals with Intellectual Development Disorder (IDD): A Scoping Review - Célia Oliveira; Sarah Ozorio; Verónica Gomes; Soraia Araújo; João Lopes (Education Sciences)
(1) Background: The experience of sexuality by individuals with Intellectual Development Disorder represents a significant challenge for themselves, as well as for parents, educators, and researchers. (2) Methods: Eighteen studies exploring sexual education programs aimed at individuals with ID and their caregivers were analyzed in the context of a scoping review. (3) Results: The prevention of sexual abuse, the development of healthy relationships, and the promotion of sexual autonomy are the main themes of the reviewed programs. The interventions include multimodal approaches, such as visual materials, practical activities, and role-playing, resulting in significant gains in participants’ sexual knowledge. Some limitations in conceptualization, participant recruitment, program variability, and the lack of follow-up were found. (4) Conclusions: Our study emphasizes the importance of expanding the research into sexual education for individuals with IDD and of designing programs with clearer theoretical frameworks, structure, and goals.